Outcomes of postnatal systemic corticosteroids administration in ventilated preterm newborns: a systematic review of randomized controlled trials - Boscarino, Giovanni; Cardilli, Viviana; Conti, Maria Giulia; Liguori, Federica; Repole, Paola; Parisi, Pasquale; Terrin, Gianluca (Frontiers in Pediatrics, 2024)
Introduction Prolonged mechanical ventilation, commonly used to assist preterm newborns, increases the risk of developing bronchopulmonary dysplasia (BPD). In recent decades, studies have demonstrated that systemic corticosteroids play a significant role in the prevention and management of BPD. In this systematic review of randomized controlled trials (RCTs), we evaluated the association between the administration of systemic corticosteroids in preterm infants and its long-term outcomes, such as neurodevelopment, growth, extubation rate, and related adverse effects. Methods We conducted an electronic search in Medline, Scopus, and PubMed using the following terms: “premature infants” and “corticosteroids.” We considered all RCTs published up to June 2023 as eligible. We included all studies involving preterm newborns treated with systemic corticosteroids and excluded studies on inhaled corticosteroids. Results A total of 39 RCTs were evaluated. The influence of steroids administered systemically during the neonatal period on long-term neurological outcomes remains unknown, with no influence observed for long-term growth. The postnatal administration of systemic corticosteroids has been found to reduce the timing of extubation and improve respiratory outcomes. Dexamethasone appears to be more effective than hydrocortisone, despite causing a higher rate of systemic hypertension and hyperglycemia. However, in the majority of RCTs analyzed, there were no differences in the adverse effects related to postnatal corticosteroid administration. Conclusion Dexamethasone administered during the neonatal period appears to be more effective than hydrocortisone in terms of respiratory outcomes; however, caution should be taken when administering dexamethasone. Data derived from current evidence, including meta-analyses, are inconclusive on the long-term effects of the administration of systemic steroids in preterm infants or the possibility of neurodevelopmental consequences.